2012
DOI: 10.33899/rjs.2012.27971
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Porphyromonas gingivalis from Periodontal Pocket Infections by Microbial Cultivation and PCR Techniques

Abstract: The study aimed to detect P. gingivalis from 49 patients with periodontitis at different ages and both sexes, after determination of pocket depth, types of infection whether chronic or progressive by dentists. Routine culture method was done using selective media and anaerobic condition and compared with species specific polymerase chain reaction (PCR) technique. DNA was extracted from samples and its concentration and purity were determined. The results showed domination of chronic infections and the pocket d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Gram positive bacteria were dominant in our study (88%), the consequences revealed that 16 (29.5) of isolate revealed positive bacterial culture of S. viridians (Table 1 & Figure 1) whereas 13 (24), 11 (20) isolates of Streptococcus. pyogenes and Staphylococcus aureus respectively with medium percentage of isolates belong to Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 51%
“…Gram positive bacteria were dominant in our study (88%), the consequences revealed that 16 (29.5) of isolate revealed positive bacterial culture of S. viridians (Table 1 & Figure 1) whereas 13 (24), 11 (20) isolates of Streptococcus. pyogenes and Staphylococcus aureus respectively with medium percentage of isolates belong to Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 51%
“…The bacteriological study including cultural properties, microscopic examination and biochemical tests was done according to MacFaddin et al, [9] ,Forbes et al, [10] . Al-Rawi [11] . "Statistical analysis castoff in this study includes calculation of mean values and percentage".…”
Section: Methodsmentioning
confidence: 99%